Inheritable testicular metabolic memory of high-fat diet causes transgenerational sperm defects in mice - Crisóstomo, Luís (2021)
Funding Information: This work was supported by the Portuguese Foundation for Science and Technology: L. Crisóstomo (SFRH/ BD/128584/2017), M.G. Alves (IFCT2015 and PTDC/MEC-AND/28691/2017), P.F. Oliveira (IFCT2015), UMIB (UIDB/00215/2020 and UIDP/00215/2020) and QOPNA (UID/QUI/00062/2019) co-funded by FEDER funds (POCI/COMPETE 2020); by the Portuguese Society of Diabetology: L. Crisóstomo and M.G. Alves (“Nuno Castel-Branco” research grant and Group of Fundamental and Translational Research); and by the European Foundation for the Study of Diabetes: L. Crisóstomo (Albert Renold Travel Grant). NMR data was collected at the UC-NMR facility which is supported in part by FEDER—European Regional Development Fund through the COMPETE Programme (Operational Programme for Competitiveness) and by National Funds through FCT— Fundação para a Ciência e a Tecnologia (Portuguese Foundation for Science and Technology) through grants REEQ/481/QUI/2006, RECI/QEQ-QFI/0168/2012, CENTRO-07-CT62-FEDER-002012, and Rede Nacional de Ressonância Magnética Nuclear (RNRMN). We thank Prof. Pedro N. Oliveira (University of Porto, Portugal) and Matthieu Bourgery (University of Turku, Finland) for their advice in Statistical Analysis. Publisher Copyright: © 2021, The Author(s). Copyright: Copyright 2021 Elsevier B.V., All rights reserved.